GERAKAN VAKSINASI COVID-19 DI BADAN KEAMANAN LAUT (BAKAMLA) REPUBLIK INDONESI (RI) - Dewi, Ratna; Nurhayati, Ety; Sukarno, Anita; Mulyana, Budi; Fatmawati, Kiki Amanda; Estheria, Estheria; Puspitasari, Rista; Renovaldi, Dede (Universitas Esa Unggul, 2021)
The addition and spread of COVID-19 cases globally is happening quite quickly, not only in the Special Capital Region of Jakarta and other densely populated cities, but has spread to rural areas in remote areas. To overcome this, the government has intensively taken steps to break the chain of transmission of COVID-19 in a fast, precise, focused, integrated, and synergistic manner between ministries/agencies and local governments. Socialization efforts were carried out related to the prevention, promotion and management of COVID through the implementation of the COVID-19 Handling Health Protocol. Other efforts have been made by various countries, including Indonesia, to develop an ideal vaccine for the prevention of SARS-CoV-2 infection with various platforms. The COVID-19 vaccination aims to reduce the transmission/transmission of COVID-19, reduce morbidity and mortality due to COVID-19, achieve herd immunity and protect the community from COVID-19 in order to remain socially and economically productive. The implementation of the COVID-19 vaccination at the Indonesian Maritime Security Agency (BAKAMLA) is a form of community service aimed at helping the government in breaking the chain of transmission of Covid-19 and accelerating the implementation of vaccinations in government employees. The vaccination takes place for 1 day with 2 (two) dose stages (Dose I and II are 14 days apart) with the type of vaccine being given, namely Sars-cov II Biofarma (Sinovac). After the service activities, most of the employees of the Indonesian Maritime Security Agency (BAKAMLA) have received the COVID-19 vaccination. Keywords : vaccine, COVID-19, BAKAMLA RI